The Bahrprobe (cruentation, ordeal of the bier) – obtaining evidence in cases of homicide in legal practice in 16th- and 17th-century Silesian and Moravian towns and the countryside - Daniel Wojtucki (Czasopismo Prawno-Historyczne, 2025)
The article describes the evidentiary method in murder trials known as the Bahrprobe, or trial by cruentation. Although classified as a type of ordeal and primarily associated with the Middle Ages, it was successfully employed during the early modern period as well. The article reconstructs the procedure of the trial by bier in the early modern era based on court records and chronicle entries. Early modern practitioners largely regarded the Bahrprobe as a legal relic, however, despite frequent criticism of the practice, it persisted in tradition and was still employed as late as the 18th century. It occurred in cases where the perpetrator of the crime was unknown or when there were multiple suspects accused of committing the crime.